Lipopolysaccharide Upregulated Intestinal Epithelial Cell Expression of Fn14 and Activation of Fn14 Signaling Amplify Intestinal TLR4-Mediated Inflammation - Qi, Xuefeng; Qin, Lijuan; Du, Ruijing; Chen, Yungang; Lei, Mingzhu; Deng, Meiyu; Wang, Jingyu (Frontiers in Cellular and Infection Microbiology, 2017)
TLR4 in intestinal epithelial cells has been shown both inflammatory and homeostatic roles following binding of its cognate ligand lipopolysaccharide (LPS). TWEAK-Fn14 axis plays an important role in pathologies caused by excessive or abnormal inflammatory responses. This study aimed to evaluate potential cross-talk between TLR4 and TWEAK/Fn14 system in porcine small intestinal epithelial cells. Our in vivo results showed that, compared with the age-matched normal control piglets, increased expression of Fn14 in epithelium and decreased TWEAK expression in lamina propria were detected in the small intestinal of piglets stimulated with LPS. Consistent with this finding, treatment with LPS increased the expression of Fn14 and TLR4 while decreased TWEAK expression in porcine small intestinal epithelial cell lines SIEC02. Interestingly, modulating Fn14 activation using agonistic anti-Fn14 decreased TLR4-mediated TNF-α production by SIEC02. In addition, pretreatment of LPS-stimulated SIEC02 with recombinant TWEAK protein suppresses the expression of Fn14 and TNF-α and inhibits the negative impact of LPS on the tight junctional protein occludin expression. In conclusion, this study demonstrates that the TWEAK-independent Fn14 activation augments TLR4-mediated inflammatory responses in the intestine of piglets. Furthermore, the TWEAK-dependent suppression of Fn14 signaling may play a role in intestinal homeostasis.